Internal Dimensions of Elementary Students' Mathematics Engagement: A Bibliometric Analysis (2019-2025) - Ikmal Choirul Huda; Arif Widiyatmoko; Sri Sumartiningsih (Elementary Teacher Education Program, Majalengka University, 2026)
Internal dimensions including motivation, self-efficacy, emotion, interest, and metacognition are critical psychological factors influencing elementary students' mathematics learning engagement. This bibliometric study examines research trends in internal dimensions from 2019 to 2025 using text mining and co-occurrence analysis. Data comprising 995 peer-reviewed articles were obtained from Google Scholar and analyzed using VOSviewer. Results identified 76 key terms forming 5 thematic clusters: (1) technology-mediated internal factors, (2) self-efficacy and achievement, (3) teacher as facilitator of internal development, (4) developmental and relational factors, and (5) motivation as core dimension. The network demonstrated high interconnection (995 links, total link strength 1,999), with self-efficacy emerging as the most researched construct. Temporal analysis revealed a paradigm shift from studying isolated psychological factors (2019-2020) toward integrated models examining multiple internal dimensions within technology-enriched learning contexts (2023-2024). Research gaps exist in developmental trajectories of internal factors across elementary grades and in mechanisms linking teacher practices to students' internal engagement. Practical implications emphasize holistic interventions simultaneously addressing motivation, self-efficacy, and mathematics anxiety through developmentally appropriate, technology-enhanced strategies. This study contributes comprehensive mapping of internal dimensions literature and identifies priorities for future research